Report on Cane and Bamboo at Agartala (Tripura) - Planning Commission (Planning Commission, 1965)
Agartala the capital of the Hill Tripura State is situated in 23' 51' N and 91"" 2 E and was the residence of the Raja of the erstwhile princely State of Tripura (Tripura). The town lies on the banks of the river Haora and the old town being on the left bank and new town on the right bank of the river. The Census of India (1961) Paper No. I of 1962 records the population of the town as 54.876 persons of whom 29,291 are males and 25,597 are females. The bulk of the present population constitutes the refugees from the East Pakistan who migrated to Agartala after the partition of the country. The climate of the place is generally fair with an annual average rainfall of 191'4 cm. The territory abounds in forests and hills well spread out and hence the name Hill Tripura State
All India Handicrafts Board
Ministry of Industry Government of India
Keywords: The Imperial Gazetteer of India mentions that Agartala; The survey of the cane and bamboo industry; Structure and Organization; The information collected for ascertaining; Production processes; and Tools & Equipment; The raw materials in bamboo is dipped; The cane and bamboo industry provides gainful employment; Wages are generally paid on the piece-rate system; The major items of raw materials required for this industry; Tripura Handicrafts Cooperative Society; Social and Living Conditions; Completely Manual